Regular and Young Investigator Award Abstracts 2020
DOI: 10.1136/jitc-2020-sitc2020.0718
|View full text |Cite
|
Sign up to set email alerts
|

718 AMG 509, a STEAP1 x CD3 bispecific XmAb®2+1 immune therapy, exhibits avidity-driven binding and preferential killing of high STEAP1-expressing prostate and Ewing sarcoma cancer cells

Abstract: BackgroundMetastatic castration-resistant prostate cancer (mCRPC) and Ewing sarcoma (EWS) are diseases for which immune therapies could potentially provide benefit. STEAP1 (Six Transmembrane Epithelial Antigen of the Prostate 1) is a cell surface protein with elevated expression in mCRPC 1 and EWS.2MethodsWe designed AMG 509, a novel, half-life extended, STEAP1 x CD3 XmAb® 2+1 bispecific antibody to induce T cell-mediated cytotoxicity against STEAP1-expressing cancer cells. AMG 509 contains two identical anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“… 49 , 65–67 Preclinical studies demonstrated AMG509-induced T-cell mediated lysis of STEAP1 expressing cancer cells in various xenograft tumor models. 68 Results from an ongoing phase I trial of AMG509 (NCT04221542) reporting data from 97 subjects with mCRPC are highly encouraging. Over half (53%) of the patients studied had radiologically visible visceral metastases at initiation of therapy and 79% of the patients had received 3 or more prior lines of therapy, including 85% of the patients who had received prior taxane-based systemic chemotherapy.…”
Section: Contemporary Bites In Clinical Studymentioning
confidence: 99%
“… 49 , 65–67 Preclinical studies demonstrated AMG509-induced T-cell mediated lysis of STEAP1 expressing cancer cells in various xenograft tumor models. 68 Results from an ongoing phase I trial of AMG509 (NCT04221542) reporting data from 97 subjects with mCRPC are highly encouraging. Over half (53%) of the patients studied had radiologically visible visceral metastases at initiation of therapy and 79% of the patients had received 3 or more prior lines of therapy, including 85% of the patients who had received prior taxane-based systemic chemotherapy.…”
Section: Contemporary Bites In Clinical Studymentioning
confidence: 99%
“…STEAP1 has become a focus of T-cell immunomodulatory drug development, with novel CAR-T and BiTE constructs actively being engineered [107][108][109] . AMG 509 is a BiTE therapy composed of two identical anti-STEAP-1 domains that have shown promising in vivo results with strong antitumor activity through increased cytotoxic T-cell activity and limited OTOT toxicity [110] .…”
Section: Six-transmembrane Epithelial Antigen Of the Prostate-1mentioning
confidence: 99%
“…AMG 509 is an Xmab ® 2+1 T-cell engager that contains two identical anti-STEAP1 Fab domains, an anti-CD3 scFv domain, and an Fc domain that prolongs serum half-life [ 78 ]. Announcing its development, Li et al described AMG 509 as having potential treatment utility for mCRPC and Ewing sarcoma.…”
Section: Steap1–4 As Biomarkers and Therapeutic Targets For Prostate ...mentioning
confidence: 99%